PEMAHAMAN TERHADAP BAHAYA SEKS BEBAS PADA PESERTA DIDIK KELAS XI SMK NEGERI 1 PONTIANAK - Pupun Tamara; Yuline, Yuline; Amallia Putri (Cahaya Ilmu Bangsa Institute, 2024)
This research aims to describe the understanding of the dangers of casual sex in class XI students at SMK Negeri 1 Pontianak. The form of research uses a study survey. The sample in this study was 42 class XI students taken using random sampling. The research method used is descriptive quantitative. Data collection using indirect communication techniques using closed questionnaires. Data analysis uses percentage correction. The results of the research show that understanding of the dangers of free sex in class XI students at SMK Negeri 1 Pontianak is 93.86% in the